CORRECTION OF EWES' REPRODUCTIVE FUNCTION IN THE EARLY POSTPARTUM PERIOD - Zhulinska, O. S.; Lobachova, I. V. (Scientific Progress & Innovations, 2020)
The results of studies on using ovine placenta tissue extracts as a means for correcting and stimulating the reproductive function of ewes in the early postpartum period are presented in the article. Two experi-ments were carried out on ewes of Ascania Fine-Fleece breed. The first experiment –I Ex, was carried out with animals of two groups: I-Ex1 – ewes with one and I-Ex2 – ewes with two lambs; for these animals, a preparation from whole placenta was used. In the second experiment – II Ex, ewes with one lamb were in-volved: for the first experimental group – II-Ex, a preparation from the whole ewe placenta was used, for the second – II-Exc from the placenta cotyledon. The preparation was injected subcutaneously three times or twice with an interval of two (3, 4, 5 ml) or three days (5 ml). The injections were started 3–5 days after de-livery. Sheep of the corresponding control groups were injected with isotonic solution according to the scheme. Regardless of the administration frequency, the preparations showed a stimulating effect on uterine contraction. After the second injection, 60–65 % of the animals had muco-bloody discharge. In the control groups (I Ex), the total number of leukocytes significantly increased: from 12.3 to 13.8 (p<0.05) and from 11.9 to 13.2 g/l (p<0.01). In experimental sheep, which were injected with the whole placenta preparation, this change was not significant – from 12.4 to 12.7 g/l. Under the action of ovine placenta tissue extracts from the whole placenta, a change in the distribution of proportions the various layers epithelial cells was observed in the cytological picture of vaginal smears, which indicated estrogen-like stimulation of prolifera-tive processes. Tissue extracts from cotyledons did not show a clear stimulating effect on proliferative pro-cesses in the vaginal epithelium (II Ex). However, in 50 % of II-Exc ewes, signs of small lymphocytes separa-tion were noticed, which was 2.5 times higher than this indicator in groups II-Ex and II-Соntrol, and the number of lymphocytes significantly increased outside the normal limits and the number of neutrophils de-creased to normal limits. In experiment I, ewes in-group Ex1 demonstrated the best reproduction rates: im-pregnation capacity 96.7, reproductive performance – 134.5 %, the final lambs number per experimental ewe – 1.16 lambs, In group I Exc, the corresponding values were the following: 88.9, 118.7 and 0.9 %, re-spectively. In the second experimental and second control groups, these indicators were as follows: 75.0 %, 100.0 %, 0.56 and 87.5 %, 114.3 %, 0.78. In experiment II, these indicators were as follows: for sheep of group II-Ex – 100.0 %, 125.0 %, 1.13, for sheep of group II-Exc - 100.0 %, 150.0 %, 1.38; for control ani-mals – 100.0 %, 120.0 %, 1.2. The revealed features of the ewes postpartum period development and the results of these studies allow to draw the following conclusions: in the postpartum period, ovine placenta tissue preparation from the whole placenta have a complex effect aimed at enhancing uterine contraction and proliferative processes in genital organs; the action of ovine placenta tissue preparation from cotyledons is more directed at stimulating hem-atopoiesis.